Formulation and Evaluation of a Pandanus amaryllifolius Leaf Ethanol Extract Ointment for Burn Wound Healing in Male Rats - Mawandha Harahap; Heppy Nova Jayanti; Bunga Salsabila Gunawan (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Burn injuries are a form of tissue trauma that remain a global health problem, with significant morbidity and mortality, especially in developing countries. Objectives: This study aims to design and evaluate the effectiveness of an ointment containing ethanol extract of Pandanus amaryllifolius Roxb. leaves as a topical agent for the healing of second-degree burns. Specifically, this research is intended to assess the pharmaceutical characteristics of the resulting formulation, including homogeneity, stability, and physical properties, to ensure product quality and consistency. Methods: Pandan leaves were selected due to their bioactive compounds, including flavonoids, tannins, alkaloids, and saponins, which possess anti-inflammatory and antibacterial properties. The ointment formulation was developed using ethanol extract of pandan leaves and its efficacy was evaluated in treating second-degree burns in male white rats induced by a heated metal plate. The investigation began with the preparation of pandan leaf extract using the maceration method with 96% ethanol as the solvent. The ointment was formulated in three concentrations: 10%, 15%, and 20%, and subsequently evaluated for physical stability. The most stable formulation was then tested on male white rats with second-degree burns. The positive control used bioplacenton ointment, while the negative control used a base ointment. Data were analyzed using normality, homogeneity, and one-way ANOVA tests. Results: The study showed that the ethanol extract of pandan leaves contains active compounds including alkaloids, flavonoids, saponins, tannins, and polyphenols. The resulting ointment had a distinctive aroma, green color, semi-solid form, and homogeneous consistency. The efficacy test results indicated a significant effect of the pandan leaf extract ointment on burn wound healing (sig. 0.000 < 0.05). Conclusion: The 20% concentration demonstrated superior efficacy in accelerating the reduction of burn wound diameter compared to the 10% and 15% concentrations. The ethanol extract of pandan leaves can be developed into an effective ointment for the treatment of second-degree burns. This ointment formulation demonstrates therapeutic effects on second-degree burn wounds in the dermis of male white rats.